WEBSITE OF EDUCATIONAL CLUSTER AS A TOOL OF OPENNESS AND PUBLICITY OF HIS ACTIVITIES - Kamalova Г.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Educational clusters, combining pedagogical universities, schools and business, provide an entirely new scientific and educational space of practice-oriented professional training of future teachers and schoolchildren based on modern cloud and distance technologies. Despite the successful functioning, their activity is still not reflected in the net and is practically inaccessible to the general public. The article substantiates the need to develop an information and educational site for the educational cluster «school - teacher training University – business» to position it on the Internet in order to attract public attention, to ensure information transparency and transparency of its activities. Its structure, composition and content of information materials published on its pages are given, the requirements for content are described.